A novel analysis-oriented theoretical model for steel tube confined ultra-high performance concrete. (15th May 2021) - Lu, Qiuru; Xu, Lihua; Chi, Yin; Deng, Fangqian; Yu, Min; Hu, Xuan
Abstract: This paper for the first time presents a newly developed analysis-oriented theoretical model for steel tube confined ultra-high performance concrete (UHPC). An active-confined UHPC model is firstly developed using experimental data collected from 62 conventional tri-axial compression tests for UHPC. Lateral strain calculation equations for both unconfined and active-confined UHPC are then proposed by using elastoplastic theory. Combined with the constitutive model of steel tube, the analysis-oriented theoretical model for steel tube confined UHPC is established and verified with available experimental results of UHPC filled steel tube (UHPCFST). Furthermore, the model's performance is evaluated with elaborations on the steel tube confinement effect and the axial stress–strain behavior of the confined UHPC for different steel tube thicknesses, steel yield strengths and UHPC compressive strengths. It is unveiled from the responses of the developed model that the confinement effect of steel tube on the core UHPC tends to be postponed for the case with higher UHPC compressive strength. The impacts on the confining stress follow an order of steel tube thickness > UHPC compressive strength > steel yield strength. Moreover, the pre-peak axial stress–strain behavior of steel tube confined UHPC is primarily determined by the UHPC compressive strength, while its post-peak behavior varies with the change in both UHPC compressive strength and steel tube thickness. The proposed theoretical model can serve as a useful tool for engineering design and nonlinear analysis of UHPCFST.